Reproductive cycle of the bivalve, Lima scabra (Pterioida: Limidae):" and its association with environmental conditions - Lodeiros, César J (Universidad de Costa Rica, 1999)
We examined the reproductive cycle of a,tropical bivalvé; the fire sdallop Lima (Ctenoides) scabra (Born, 1778), over a 14 months period in the Golfo de Cariaco, Venezuelá, and the' assooiation of gonadal gtowth